MARINE ECOTOURISM POTENTIAL OF BATUKALANG BEACH PESISIR SELATAN DISTRICT WEST SUMATERA PROVINCE - Mhd. Fadhillah, Mhd. Fadhillah; Yoswaty, Dessy; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe aim of the study was to discover the potential level of Batukalang Beach as destination for marine ecotourism. The method used was survey methods, data was consisting of primary and secondary data. Interviewing sampling method was used purposively, particularly for tourist sample for local people, stakeholder and local goverment. The result showed that Batukalang Beach has a big potential in marine tourism and possess a big chance to develop in marine ecotourism sector. It was showed by the suitability value of marine ecotourism development. The value was resulted through tourism proponent criteria, total scores of WTA and WTP, scores of economic potential, and SWOT analysis. Key Words: Batukalang, potential and marine ecotourism